20 SRC members promised to carry out their duties - UMP, PNC

(untitled)
Twenty Universiti Malaysia Pahang (UMP)'s Student Representative Council (SRC) members for 2012/2013 session, led by its president Abdul Na'em Suhaime, took their oath of duty and loyalty before its Vice-Chancellor, Professor Dato' Dr. Daing Nasir Ibrahim and the top management team.